An asymptotic streamline diffusion finite element method for singularly perturbed convection‐diffusion delay differential equations with point source. Issue 6 (14th October 2021) - Sethurathinam, Senthilkumar; Veerasamy, Subburayan; Arasamudi, Rameshbabu; Agarwal, Ravi P.
Abstract: In this article, we presented an asymptotic SDFEM for singularly perturbed convection diffusion type differential difference equations with point source term. First, the solution is decomposed into two functions, among them one is the solution of delay differential equation and other one is the solution of differential equation with point source. Furthermore, using the asymptotic expansion approximation, the delay differential equation is modified as a nondelay differential equations. Streamline diffusion finite element methods are applied to approximate the solutions of the two problems. We prove that the present method gives an almost second‐order convergence in maximum norm and square integrable norm, whereas first‐order convergence in H 1 norm. Numerical results are presented to validate the theoretical results.